Maternal obesity, pregnancy weight gain, and birth weight and risk of colorectal cancer. Issue 7 (24th August 2021) - Murphy, Caitlin C; Cirillo, Piera M; Krigbaum, Nickilou Y; Singal, Amit G; Lee, MinJae; Zaki, Timothy; Burstein, Ezra; Cohn, Barbara A
Abstract : Objective: Colorectal cancer (CRC) is a leading cause of cancer-related death worldwide. Obesity is a well-established risk factor for CRC, and fetal or developmental origins of obesity may underlie its effect on cancer in adulthood. We examined associations of maternal obesity, pregnancy weight gain, and birth weight and CRC in adult offspring. Design: The Child Health and Development Studies is a prospective cohort of women receiving prenatal care between 1959 and 1966 in Oakland, California (N=18 751 live births among 14 507 mothers). Clinical information was abstracted from mothers' medical records 6 months prior to pregnancy through delivery. Diagnoses of CRC in adult (age ≥18 years) offspring were ascertained through 2019 by linkage with the California Cancer Registry. We used Cox proportional hazards models to estimate adjusted HR (aHR); we examined effect measure modification using single-referent models to estimate the relative excess risk due to interaction (RERI). Results: 68 offspring were diagnosed with CRC over 738 048 person-years of follow-up, and half (48.5%) were diagnosed younger than age 50 years. Maternal obesity (≥30 kg/m 2 ) increased the risk of CRC in offspring (aHR 2.51, 95% CI 1.05 to 6.02). Total weight gain modified the association of rate of early weight gain (RERI −4.37, 95% CI −9.49 to 0.76), suggesting discordant growth from early to late pregnancy increases risk. There was an elevated association with birth weight (≥4000 g: aHR 1.95, 95% CI 0.8 to 4.38). Conclusion: Our results suggest that in utero events are important risk factors for CRC and may contribute to increasing incidence rates in younger adults.